30‐Lens interferometer for high‐energy X‐rays. (9th August 2016) - Lyubomirskiy, Mikhail; Snigireva, Irina; Kohn, Victor; Kuznetsov, Sergey; Yunkin, Vyacheslav; Vaughan, Gavin; Snigirev, Anatoly
Abstract : A 30‐lens interferometer was designed, manufactured and tested at X‐ray energies from 30 to 65 keV. The interferometer was used to measure an effective source (FWHM) of 15 µm from the interference pattern recorded at the fundamental Talbot distance. Abstract : A novel high‐energy multi‐lens interferometer consisting of 30 arrays of planar compound refractive lenses is reported. Under coherent illumination each lens array creates a diffraction‐limited secondary source. Overlapping such coherent beams produces an interference pattern demonstrating strong longitudinal functional dependence. The proposed multi‐lens interferometer was tested experimentally at the 100 m‐long ID11 ESRF beamline in the X‐ray energy range from 30 to 65 keV. The interference pattern generated by the interferometer was recorded at fundamental and fractional Talbot distances. An effective source size (FWHM) of the order of 15 µm was determined from the first Talbot image, proving the concept that the multi‐lens interferometer can be used as a high‐resolution tool for beam diagnostics.